Ketidakseimbangan Penentuan Klausula Baku dalam Kontrak Pembiayaan Modal Kerja: (Studi Putusan No. 13/Pdt.G/2011/Pn. End) - Muhairir, Mulia Aqsa; Harahap, Mhd Yadi (Legal Standing : Jurnal Ilmu Hukum, 2025)
Standard clauses that are imbalanced in working capital financing contracts, with a case study on Decision No. 13/Pdt.G/2011/PN. End. The approach used is normative juridical, by examining laws and regulations, doctrines, and judicial considerations. Data were collected through library research covering various legal sources, including primary materials such as the Indonesian Civil Code (KUHPerdata), Law Number 8 of 1999 concerning Consumer Protection (UUPK), and Decision No. 13/Pdt.G/2011/PN.End. Secondary materials used include legal books and journals. Tertiary materials include legal dictionaries and encyclopedias. The results show that clauses granting unilateral authority to the business party, eliminating the debtor’s right to objection, and establishing irrevocable absolute power have violated the principle of contractual justice and the provisions of Article 18 of Law Number 8 of 1999 concerning Consumer Protection. Such clauses are declared null and void because they fail to meet the elements of free agreement and lawful cause in contract law. Therefore, there needs to be a reassessment of the practice of standard contracts in the financing sector to ensure fair legal protection for consumers.